Removal of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) from water by carbonaceous nanomaterials: A review. Issue 22 (16th November 2020) - Liu, Longfei; Liu, Yanli; Gao, Bin; Ji, Rong; Li, Chengliang; Wang, Shengsen
Abstract: Per- and polyfluoroalkyl substances (PFASs) are commonly used in many consumer and industrial products. However, their resulting widespread release into aqueous environments and their potential toxicities to organisms have raised significant environmental concern. Among the various approaches to the removal of PFAS contaminants, adsorption has proven to be highly effective, especially when carbonaceous nanomaterials (CNMs) are used as the adsorbent. Nonetheless, the interfacial adsorption of PFASs on CNMs is affected by many factors. In this work, the adsorption behaviors of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS), two highly representative PFASs, on different CNMs are reviewed. We also examine the mechanisms of PFOA and PFOS adsorption on CNMs, including electrostatic and hydrophobic interactions, ligand exchange and hydrogen bonding. Due to the significant influence of hydrophobic interactions on adsorption, CNMs rich in oxygen-containing functional groups will result in weaker PFAS adsorption than achieved using pristine materials. The important contribution of nanobubbles to hydrophobic interactions is considered herein. Overall, this work contributes to a better understanding of the adsorption affinity of PFASs on CNMs in water environments. Moreover, it provides the systematic theoretical support that is needed for the more effective use of CNMs in the removal of PFASs from aqueous systems. Graphical Abstract: UF0001